Modelagem dinâmica de uso e cobertura da terra da bacia do Arroio Grande - RS - Furlan, Mariele Coletto (2012)
Located on the mid-region of Rio Grande do Sul, the watershed of the Arroio Grande lies on the transition of the Central Depression to the Southern Plateau. Belonging to the geographic micro-region of Santa Maria, the watershed area partially covers four municipal districts: Silveira Marins, Itaara, Santa Maria and Júlio de Castilhos. Studies on the area showed, on the last two decades, a local increase tendency of the forest areas, rural activities and a decrease of the field areas. This work had as objective, modeling the dynamics of use and covering of land occurred in two periods of time: from 1991 to 2002 and from 2002 to 2011; and to perform the simulation of scenarios until the year of 2020. To elaborate the thematic maps of land cover and use, images the satellites Landsat 5 and Landsat 7 were classified. The modeling process was performed by the Dinamica EGO app through these methods: Markov Chain, Weights-of-Evidence and Cellular Automata. The simulated maps to the years of 2002 e 2011, when compared with real maps, reached satisfactory similarities indexes. The simulated scenery for the year of 2020 presented significant less percentages of changing of the use and cover than those verified for the previous periods, predicting increase of 2,64% and 4,38% to the forest and rural areas respectively, and a decrease of the field areas about 8,19%. This dynamic may indicate stagnation in the agricultural cultivation areas, because there are no great extensions of proper land for the agricultural advance, which is the main propeller of the observed evolution in the study period, on the regions of greater agricultural vocation, as it is on the proximities of Silveira Martins, in the floodplain of Arroio Grande and in Southern Plateau areas, corresponding to Júlio de Castilhos.